Print Rights with a Thousand Masks: Migrant Vulnerability, Resistance and Human Rights Law - Dez, Jordan F. (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2022)
PrintRights, a co-operative of undocumented asylum seekers in Amsterdam, manufactured facemasks during the COVID-19 pandemic, first distributing them to undocumented migrants residing in the city’s emergency shelter system and then selling them to the wider public. By distributing facemasks with messages, PrintRights framed its action within the human right to freedom of expression to legally resist alienage law prohibitions on employment. Engaging Judith Butler’s theory, this article analyzes the relationship between PrintRights’ resistance, vulnerability, and strategic engagement with human rights law. Drawing on fieldwork conducted with PrintRights, I explore how vulnerability discourse in human rights law can support undocumented migrant organizing.